Adolescence to Young Adulthood: When Socioeconomic Disparities in Substance Use Emerge. (6th December 2013) - Widome, Rachel; Wall, Melanie M.; Laska, Melissa N.; Eisenberg, Marla E.; Neumark-Sztainer, Dianne
<x xml:space="preserve">Abstract</x> We examined trends in cigarette, alcohol, and marijuana use by eventual educational attainment in 1, 902 participants from Project EAT, a 10-year longitudinal study following participants from early adolescence through young adulthood. Generally, for cigarettes and marijuana, disparities were evident by early adolescence with prevalence of use highest among those who had no secondary education. With alcohol, use diverged during young adulthood when the college group reported the most weekly alcohol use while those without postsecondary education reported greatest daily use. When disparities in substance use behaviors first emerge and later escalate can guide how to craft and target interventions.